2017
DOI: 10.1155/2017/2515408
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine Alters Inflammatory and Oxidative Stress Molecular Markers in Arthritis

Abstract: Buprenorphine is recommended for use as an analgesic in animal models including in murine models of collagen-induced arthritis (CIA). However, the effect of buprenorphine on the expression of disease-associated biomarkers is not well defined. We examined the effect of buprenorphine administration on disease progression and the expression of inflammatory and oxidative stress markers, in a murine model of CIA. Buprenorphine administration altered the expression of cytokines, IFN-γ, IL-6, and MMP-3, and oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 23 publications
4
36
0
Order By: Relevance
“…In addition, methadone seems to have a more severe effect as indicated by the significantly lower values of catalase compared to buprenorphine. These results are supported by previous findings [4952]. Specifically, methadone appears to have a greater impact on lowering antioxidant defence since patients under MMT have shown a depletion of GSH and CAT levels [50, 52].…”
Section: Discussionsupporting
confidence: 90%
“…In addition, methadone seems to have a more severe effect as indicated by the significantly lower values of catalase compared to buprenorphine. These results are supported by previous findings [4952]. Specifically, methadone appears to have a greater impact on lowering antioxidant defence since patients under MMT have shown a depletion of GSH and CAT levels [50, 52].…”
Section: Discussionsupporting
confidence: 90%
“…The protocol used for the CIA murine model was based on our previous study [ 30 ] and approved by The University of Manitoba Animal Research Ethics Board. Experimental design and reporting of data is compliant with the ARRIVE guidelines for in vivo animal research [ 34 ].…”
Section: Methodsmentioning
confidence: 99%
“…These synthetic peptides were resuspended in sterile saline and administered by s.c. injections (6 mg/kg body weight) in both models. The dose and mode of administration of these peptides were based on our previous studies in the CIA model and HDM-challenge model (24)(25)(26)(27). In the CIA model, the peptides were administered starting from day 20 [1 day before boost, after the initial arthritis induction phase (32)] and subsequently every 48 h until the end of the study.…”
Section: Administration Of Cathelicidin-derived Synthetic Peptides Inmentioning
confidence: 99%
“…In this study, we investigated the abundance of the mouse cathelicidin CRAMP, α -and β-defensins, and calprotectin subunits S100A8 and S100A9, in the two different murine models of chronic inflammation; a CIA model of inflammatory arthritis and allergen HDM-challenged model of airway inflammation (25)(26)(27). We showed that CRAMP and calprotectin subunits S100A8, and S100A9 are disparately altered in these mouse models, being significantly increased in the joint tissues of CIA mice, but decreased in the HDM-challenged lungs.…”
Section: Introductionmentioning
confidence: 99%